Sintesis dan Potensi Aktivitas Tabir Surya Senyawa Analog Kalkon Turunan 3’-Hidroksiasetofenon dan 4-Metoksibenzaldehid - Ihsan Ikhtiarudin; Nesa Agistia; Tria Harlianti; Adel Zamri (LPPM Universitas Muhammadiyah Riau, 2019)
Chalcone analogues have attracted the attention of researchers due to their various biological activities. In this study, a chalcone analogue, (E)-1-(3-hydroxyphenyl)-3-(4-methoxyphenyl)prop-2-en-1-on has been synthesized under microwave irradiation and its sunscreen activity has been evaluated by in vitro assay using 96-well microplate reader. Based on the in vitro assay, at concentration of 100-500 µg/ml, the compound showed potential sunscreen activity with %Te value of 5.49 – 0.04 % (extra protection – sunblock), %Tp value of 0.51-0.05 % (sunblock) and SPF value of 18.20 – 32.91 (ultra protection). The assay result showed that the (E)-1-(3-hydroxyphenyl)-3-(4-methoxyphenyl)prop-2-en-1-on has a potency to be developed as active ingredient in sunscreen product.